Effect of Acute Toxicity of Commercial Organophosphate Insecticide Based on Chlorpyrifos on Fejervarya limnocharis Tadpoles (Anura: Dicroglossidae): Acute Toxicity of Commercial Chloropyrifos on Fejervarya limnocharis Tadpole - Shima Ramadani; Agung Pramana Warih Marhendra; Dewa Gede Raka Wiadnya; Nia Kurniawan (Journal of Tropical Life Science, 2022)
Organophosphate pesticides, especially chlorpyrifos, are one of the most widely used insecticides in agriculture, but their toxicity and potential sensitivity effects on Anura, especially Fejervarya limnocharis are still unknown. The purpose of this investigation is to study F. limnocharis (Anura: Dicroglossidae) tadpole sensitivity to lethal (survivability) and sublethal effects (morphological alterations and swimming activity) of chlorpyrifos in Dursban 200EC commercial formula under acute exposure. An acute toxicity test was carried out on ten tadpoles (Gosner 25) in each repetition. The sample was obtained from artificial reproduction by injecting the Trial Batch 2000 IU hCG by Kings Lab. The acute toxicity testing consisted of three replicates with a chlorpyrifos concentration of 0; 0.4; 0.8; 1; 2; 4; and 8 µg/L. Physico-chemical parameters, mortality, morphological, and swimming alterations of each concentration were observed at 24th, 48th, 72nd, and 96th hours. The LC50 of chlorpyrifos for F. limnocharis tadpoles was 2.86 µg/L. The percentage of survivability F. limnocharis tadpoles decreased after exposure to chlorpyrifos above 1µg/L, while morphological alterations were observed in 2 µg/L and 4 µg/L after 48th hours exposure, and the swimming alterations have occurred at 24th hours in 1; 2; 4 and 8 µg/L. Morphological alterations were observed including asymmetrical body shape, edema, and abnormal tail shape. Based on the LC50 value, commercial chlorpyrifos has high-level toxicity on F. limnocharis tadpoles.Keywords: Acute, Chlorpyrifos, Dursban 200 EC, Fejervarya limnocharis, Tadpoles